PERAN MATA PELAJARAN BAHASA INDONESIA DALAM MEMBENTUK PROFIL PELAJAR PANCASILA - Frilia Shantika Regina; Andoyo Sastromiharjo (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This study aims to describe the role of Indonesian language subjects in forming the Pancasila Student Profile. The method used in this research is descriptive qualitative method. The research data was obtained based on the results of the questionnaires which were distributed to Indonesian language subject teachers who were implementing the Mobilization School Program. Based on the results of this study, it can be concluded that each teacher has carried out a learning process that can improve the six dimensions of the Pancasila Student Profile, namely 1) fear of God Almighty, and have noble character; 2) global diversity; 3) work together; 4) independent; 5) critical reasoning; 6) creative. From the six Pancasila Student Profiles, all dimensions can be improved in Indonesian language subjects by combining several dimensions in the learning process because in essence each dimension must be related to other dimensions in a process.